Parrhesia and Pedagogy: About the posibility of an education with parrhesia at present - Soto Méndez, Katalina (Revista Ethika+, 2020)
The main purpose of this paper to treat the possibility of a parresiasic education at present. The difficulty arises when considering contemporary educational methods, since they have a practical and controlling approach. However, I reckon the possibility of thinking about a parrhesiastic pedagogy implies considering other, less conventional, educational methods, specifically the one of the philosopher Matthew Lipman. Then, this article aims to rescue the parrhesia’s characters that are present in that program and note the importance of a training with the presence of parrhesia.